ASSESSMENT OF Moringa oleifera LEAF-MEAL EXTRACTS DIETS USING DIFFERENT SOLVENTS ON GROWTH AND HAEMATOLOGICAL PARAMETERS OF Clarias gariepinus - Mohammed, Suleiman Adamu; Abdul-Azeez, Hassan (Nigerian Journal of Fisheries, 2025)
This study evaluated the effects of combined Moringa oleifera leaf meal extracts, solvent-extract combinations, and inclusion ratios on the growth performance and haematological parameters of Clarias gariepinus. A total of 960 juveniles (9.8 ± 0.1 g) were used in a 56-day feeding trial arranged in a 3 × 5 factorial design, comprising three extract combinations (aqueous + ethanol, MAE; ethanol + hexane, MEH; aqueous + hexane, MAH) and five inclusion ratios (0:100, 25:75, 50:50, 75:25, and 100:0%), resulting in fifteen treatments with three replicates each. Fish were fed at 5% body weight, twice daily. Both extract combination and inclusion ratio significantly affected (p < 0.05) growth and feed utilization parameters, except apparent net protein utilization and survival, while interaction effects were not significant. Diets containing MAE and MEH at 100:0% produced the highest mean weight gain, specific growth rate (3.84–3.96% day⁻¹), protein efficiency ratio (2.14), and survival (88.33–100%), and the lowest feed conversion ratio (1.01–1.06). Haematological indices were significantly influenced (p < 0.05), with superior treatments recording higher red blood cell counts (up to 4.10 × 10¹² L⁻¹), haemoglobin (11.00 g dL⁻¹), and packed cell volume (33.00%).The results indicate that polar solvent combinations, particularly MAE at higher inclusion ratios, enhance growth performance and physiological status of C. gariepinus, confirming M. oleifera leaf meal extract as an effective and sustainable aquafeed additive. The study concludes that M. oleifera leaf extracts, particularly when extracted with polar solvents like water and ethanol, serve as effective growth enhancers and immunostimulants, optimizing both the growth and health status of C. gariepinus. Keywords: Aquaculture, Medicinal, Nutrition, Solvent and Plant